PACTO NACIONAL PELA ALFABETIZAÇÃO NA IDADE CERTA: UMA ANÁLISE CONTEXTUAL DA PRODUÇÃO DA POLÍTICA E DOS PROCESSOS DE RECONTEXTUALIZAÇÃO - Alferes, Marcia Aparecida (2017)
This thesis analysis the production of PNAIC (National Pact for Literacy in the Right Age, in its Portuguese acronym) in Federal Government scope (macro level) and how the actions of the Program were recontextualized by study supervisors and literacy teachers in continuous training (meso level), and inside the classroom by literacy teachers (micro level). It used concepts by Bernstein (1996, 2003) theory on structuration of pedadogical discourse and recontextualization process, as well contributions from the theory of policy enactment by Ball, Maguire and Braun (2016). The research had as base a qualitative study focused on the following aspects: a) study supervisors and literacy teachers continuous; and b) on literacy pedagogical practices developed with 1st, 2nd and 3rd years of Elementary School. It was developed in two schools of teaching municipal network of Ponta Grossa/PR. Data collection procedures were performed in the analysis of official and legal documents of PNAIC. In addition, the participant observation on the continuous training of study supervisors and literacy teachers in events carried out by the Municipal Secretary of Education and PNAIC Coordination of Ponta Grossa State University were consider for data collection. Participating observation on pedagogical practices in the literacy cycle (1st, 2nd and 3rd years on Elementary School) inside classrooms of two schools in Ponta Grossa town, state of Paraná were carried out for data collection. Interviews with PNAIC general coordinator; PNAIC local coordinator; PNAIC trainer; study supervisor; management and pedagogical team of two schools of municipal education network of Ponta Grossa, Paraná; and literacy teachers also composed the data collection. The thesis argued that PNAIC has elements of a mixed pedagogy based on the pedagogical models of competence and performance. Likewise, the study argued that PNAIC is recontextualized in meso and micro instances setting up different meanings and possibilities in the process of enactment. The results of the research indicate that, although comprehensive, necessary and relevant, the National Pact for Literacy at the Right Age (called PNAIC) presents potentialities, limits and challenges. Some of the potentialities are: PNAIC is a comprehensive program with well defined actions and strategies; it has specific materials for literacy classes; it takes advantage of school existing materials; it makes possible the participation of public universities in the elaboration of the material and education of teachers; it provides greater visibility of the areas of Geography, Art, History and Science, among others. As limitations, the main one is the discontinuity of PNAIC. In addition, there was no accountability for the investments made in the program; not all teachers who participated in the courses remained in the literacy cycle; the financial resources are not passed directly to the universities; and there is no democratic space to publicly debate PNAIC, with the teachers’ participation. The challenges are: the continuity of the program from a network education perspective; discussions about education and the role of the school; improvement in the material and working conditions of the teachers; pedagogical support for teachers at school, specially for beginners; constant monitoring of student learning; curriculum revision of teacher education courses